Corrosion-resistant magnesium alloy for 5G base station shell, preparation method and application
By adding elements such as Zr and Nd to the magnesium alloy to form a corrosive surface film with nano-microstructures, the problem of insufficient corrosion resistance of magnesium alloys in 5G base stations is solved, and the service life is significantly extended.
Patent Information
- Application Number
- CN202411997540.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
During the use of 5G base stations, magnesium alloys have poor corrosion resistance, especially under the service conditions of alternate cold and heat cycles, which lead to corrosion of components, affecting their service life.
By adding elements such as Zr and Nd to the magnesium alloy matrix through microalloyization, a corrosion surface film with nano-microstructure is formed to enhance the corrosion resistance of the alloy.
It realizes that the corrosion surface film is kept dense under high and low temperature cycle conditions, without obvious cracks, and extends the service life of the 5G base station shell.
Smart Images

Figure CN119800181A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and specifically to a corrosion-resistant magnesium alloy for a 5G base station housing, a preparation method and applications thereof. Background Art
[0002] 5G base stations are the core equipment of 5G networks. They can provide wireless coverage and realize wireless signal transmission between wired communication networks and wireless terminals. The architecture and form of base stations directly affect how 5G networks are deployed. With the acceleration of 5G network construction, it is expected that the number of 5G base stations in the country will exceed 600,000 by the end of the year, which will realize the deployment of outdoor continuous coverage in prefecture-level cities, key coverage in county towns and townships, and indoor coverage in key scenarios.
[0003] The power consumption of 5G base stations is about 2.5-3 times that of 4G. As the size of 5G base stations is developing towards small and lightweight, the hot and cold cycles of 5G base stations during use are more obvious. Magnesium alloy has become one of the important metal materials used in 5G base stations due to its fast and easy molding and outstanding lightweight effect.
[0004] However, due to the poor corrosion resistance of magnesium alloys, especially under the service conditions of alternating hot and cold cycles, its corrosion-resistant surface film will quickly crack and fail, which will lead to corrosion of components. The invention patent with announcement number CN104264021B and titled "A Corrosion-Resistant Magnesium Alloy" also mentioned that the corrosion resistance of magnesium alloys has become an obstacle to the industrial application of magnesium alloys. The purpose of this patent is also to prepare a corrosion-resistant magnesium alloy material. In the application field of the present invention, 5G base stations, there is also a problem, that is, during the actual service of the 5G base station, condensed water will inevitably be generated inside the shell. This corrosion behavior of the thin liquid film in the atmospheric environment seriously affects the service life of the base station.
[0005] In summary, it is very necessary to develop a new type of magnesium alloy material that can withstand high and low temperature cycles, overcome the shortcomings of magnesium alloys that are difficult to serve for a long time in the above-mentioned harsh environment, further give play to the advantages of magnesium alloys in lightweight, and improve the competitiveness of magnesium alloys in the application of 5G base stations. Summary of the invention
[0006] Based on the above problems, the present invention provides a corrosion-resistant magnesium alloy for a 5G base station shell, a preparation method and an application. The present invention aims to add elements that can participate in corrosion reactions and generate nano-microstructures inside the corrosion surface film to the magnesium alloy matrix through a microalloying method.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: A corrosion-resistant magnesium alloy for a 5G base station shell consists of the following components in mass percentage: a Zr content of less than 0.2%, a Nd content of between 2.5% and 3%, and the remainder being Mg.
[0008] Furthermore, the Zr can be replaced by any one of Ti and Sn, and the Nd can be replaced by any one of Sm, Eu and Pr. Furthermore, the raw materials of the corrosion-resistant magnesium alloy are Mg30Nd alloy and Mg10Zr alloy.
[0009] Furthermore, the average grain size of the corrosion-resistant magnesium alloy is 10-20 μm.
[0010] Furthermore, an island-shaped Zr-rich area is formed in the corrosion-resistant magnesium alloy.
[0011] In order to solve the above technical problems, the present invention also provides the application of corrosion-resistant magnesium alloy in 5G base station housing.
[0012] In order to solve the above technical problems, the present invention also provides a method for preparing a corrosion-resistant magnesium alloy, comprising the following steps: S1: proportioning the raw materials; S2: the alloy in step S1 is placed in a graphite crucible, heated to 720° C. and kept at this temperature for 30 minutes, and then further heated to 780° C., kept at this temperature for 30 minutes, and then cooled with the furnace to obtain an ingot; S3: keeping the ingot obtained in step S2 at 535° C. for 16 hours, and then quenching with 80° C. hot water; S4: keeping the material processed in step S3 at 220° C. for 32 hours, and air-cooling to obtain a corrosion-resistant magnesium alloy sample.
[0013] Compared with the prior art, the present invention has the following beneficial effects: the average grain size of the novel corrosion-resistant magnesium alloy prepared by the present invention is 10-20 μm, and a Zr-rich nanoshell structure exists inside the corrosion surface film thereof. The nanoshell structure is generated in situ in the corrosion film through the corrosion process, and is denser than the conventional magnesium oxide corrosion surface film, and the stress release is more uniform, so that the film layer will not crack during the high and low temperature cycle process; The corrosion surface film of the corrosion-resistant magnesium alloy of the present invention can remain dense during high and low temperature cycles (5°C-65°C) without forming obvious cracks. The corrosion-resistant magnesium alloy serves as an effective barrier to isolate corrosive media and can effectively maintain the corrosion resistance of the base station shell during the operation of the base station, thereby extending the service life of the base station shell and having good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1The SEM images of typical alloy matrices of the embodiments of the present invention are as follows: (a) Mg3Nd; (b) Mg3NdZr; Figure 2 The macroscopic SEM images of typical alloy substrates after corrosion testing of the embodiments of the present invention are as follows: (a) Mg3Nd; (b) Mg4Nd0.2Zr; (c) Mg3Nd0.5Zr; (d) Mg0.2Zr; (e) Mg3Nd0.2Zr; Figure 3 The internal shell structure of the Mg3Nd0.2Zr alloy corrosion film layer of the embodiment of the present invention; Figure 4 These are cross-sectional photos of Mg3Nd0.2Zr alloys after corrosion by different smelting processes according to the embodiments of the present invention, where (a) 1#; (b) 2#; Figure 5 This is a polarized photo of the substrate of the Mg3Nd0.2Zr alloy after 535-16h treatment according to an embodiment of the present invention; Figure 6 The cross-section of the corrosion film layer of the Mg3Nd0.2Zr alloy of the embodiment of the present invention after different heat treatment processes, wherein: (a) 500-16h; (b) 535-16h; Figure 7 The stress distribution inside the corrosion film of the Mg3Nd0.2Zr alloy of the embodiment of the present invention after different heat treatment processes, where: (a) 500-16h; (b) 535-16h; Figure 8 This is the macroscopic morphology of the conventional ZM5 after corrosion under high and low temperature cycle conditions of the embodiment of the present invention; Fig. 9 This is the macroscopic morphology of the new corrosion-resistant magnesium alloy after corrosion under high and low temperature cycle conditions according to the embodiment of the present invention. DETAILED DESCRIPTION
[0015] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0016] Example: In order to obtain a new type of corrosion-resistant magnesium alloy, the inventors first need to screen suitable elements as nucleation centers. Suitable elements must react before other elements to form corresponding hydroxides during the corrosion reaction. The inventors found through screening of the thermodynamic database that Zr, Ti, Sn and other elements can be used as nucleation center elements to form a shell structure. At the same time, the inventors also fully considered the solubility of such elements in Mg during the actual corrosion process to minimize the formation of the second phase and weaken the microgalvanic effect during the corrosion process. The inventors preliminarily determined through phase diagram analysis that the content of the screened nucleation center elements should be below 0.5wt%.
[0017] The contribution of the above-mentioned elements as the core of the shell structure in the actual corrosion surface film formation process, that is, the crystallization process, is affected by the interface matching ability. When the interface matching ability is poor, this type of nucleation center point element cannot contribute to the promotion of the nanoshell structure. Through the calculation of Bramfitt's two-dimensional mismatch, it is found that rare earth elements represented by Nd can show good matching ability with magnesium hydroxide (the main structure of the corrosion surface film), thereby promoting the formation of nanoshell structure.
[0018] In this embodiment, the inventors synthesized MgNdZr alloy using Zr, Nd and Mg as raw materials, and determined that the content of Zr was less than 0.2%, the content of Nd was between 2.5-3%, and the balance was Mg. Among them, Zr is an element that is easily precipitated in the corrosion reaction, and Nd is an element that has good interface matching ability with Mg hydroxide.
[0019] The raw materials used by the inventors in preparing the MgNdZr alloy are Mg30Nd alloy and Mg10Zr alloy. The specific preparation method is as follows.
[0020] First, alloy smelting is carried out. The raw materials are high-purity magnesium: Mg30Nd alloy and Mg10Zr alloy. According to the mass percentage conversion mentioned above, Mg30Nd alloy and Mg10Zr alloy are proportioned. Before smelting, it is necessary to remove oil and oxide scale from the surface of each raw material to ensure that the raw materials are clean and tidy.
[0021] Melting environment requirements: In order to reduce the loss during the melting process and additional external pollution, the alloys in the present invention all adopt a vacuum melting environment and a tilting melting furnace equipment.
[0022] Melting temperature requirements: put the prepared alloy material into a graphite crucible, heat the temperature to 720℃ and keep it warm for 30 minutes (to allow magnesium to fully melt), then further heat it to 780℃ (to allow the MgZr master alloy to melt), then keep it warm for 30 minutes and cool it with the furnace to obtain the corresponding ingot.
[0023] Next, heat treatment is performed. The heat treatment of the present invention is carried out by solution treatment plus artificial aging treatment to adjust the matrix element distribution and grain size. In order to ensure that the alloy elements fully participate in the corrosion reaction and enter the interior of the corrosion surface film, the heat treatment process of the present invention is as follows: (1) Solution treatment: keep the temperature at 535°C for 16 hours, and then quench with hot water at 80°C; this step can ensure the full dissolution of alloy elements and the uniformity of matrix structure; since the present invention is mainly aimed at the shell design of 5G base stations under high and low temperature cycle loads, the requirements for mechanical properties are not strict. The grain boundaries of the matrix are usually used as weak locations of corrosion surface films. The solution treatment temperature and time of the present invention are intended to control the appropriate matrix grain size so that the grain size is not too large (poor mechanical properties) or too small (too many grain boundaries can easily cause film cracking); (2) Artificial aging: Keep at 220°C for 32 hours and air cool; this step aims to further homogenize the structure.
[0024] After the above treatment, the average grain size of the magnesium alloy obtained is controlled at 10-20μm, which not only ensures certain mechanical properties but also minimizes the weak areas of the film layer; at the same time, an island-shaped Zr-rich area is formed, which can promote the formation of nanoshell structure during corrosion.
[0025] Next, the inventors conducted a high and low temperature cyclic corrosion test on the obtained magnesium alloy material. The test was carried out in a high and low temperature wet heat test chamber, with a cycle of 24 hours, and two cycles of testing were performed. The corrosion rate was then calculated, and the test was carried out with reference to the national standard GBT 16545-2015 Corrosion of metals and alloys, and the removal of corrosion products on corrosion specimens was tested. The corrosion rate calculation formula is as follows: R=(W2-W1) / t Where R is the corrosion rate, W1 is the weight before corrosion, W2 is the weight after corrosion, and t is the test time This embodiment compares the corrosion rates of Mg3Nd, Mg3Nd0.2Zr, Mg4Nd0.2Zr, Mg3Nd0.5Zr, and Mg0.2Zr alloys prepared by the above method under high and low temperature cycles to illustrate the effect of the shell structure on high and low temperature cycle corrosion. See the table below, where the numbers represent mass fractions. For example, in Mg3Nd0.2Zr, 3 represents the mass percentage of Nd, 0.2 represents the mass percentage of Zr, and the other components are represented by analogy. It can be seen from the table that the corrosion rate of the alloys within the required range of the present invention is significantly lower.
[0026]
[0027] The SEM images of typical alloy substrates and the SEM images of the macroscopic morphology of typical alloy substrates after corrosion testing are shown in the attached Figure 1 and attached Figure 2 The internal shell structure of the Mg3Nd0.2Zr alloy corrosion film is shown in the attached Figure 3 .
[0028] From the macroscopic morphology of corrosion, it can be seen that the corrosion of alloys whose component contents are not within the required range of the present invention is relatively serious, and obvious pitting pits appear. Figure 2 Figure e in the figure is within the required range of the present invention, and it can be seen that the corrosion is much lighter. This is because the content of the Nd element needs to be controlled within a certain range, thereby reducing the formation of precipitated phases to form serious micro-galvanic corrosion; while the excessive content of the Zr element will also lead to the formation of new precipitated phases, promote corrosion reactions, and the resulting hydrogen bubbles will interfere with the compactness of the corrosion surface film.
[0029] The corrosion-resistant magnesium alloy of the present invention can exhibit good corrosion resistance to high and low temperature cycles, mainly due to the presence of a nano-scale shell structure in its corrosion surface film, which can effectively densify the film layer and fully release the stress of the film layer during high geothermal cycles, thereby reducing its cracking tendency.
[0030] Next, the inventors compared the corrosion rates of Mg3Nd0.2Zr alloys produced by gravity smelting casting process 1# and vacuum tilting smelting process 2# under high and low temperature cycles to illustrate the role of smelting process optimization. The corrosion rate comparison is shown in the following table:
[0031] In addition, see attached Figure 4 , which are cross-sectional photographs of Mg3Nd0.2Zr alloy after corrosion by different smelting processes. It can be seen that the smelting process of the present invention is significantly superior to the smelting process of the prior art, and the Mg3Nd0.2Zr alloy prepared by the smelting process of the present invention has excellent corrosion resistance.
[0032] The inventors conducted a comparative study on different solution treatment conditions. See the table below, which shows the mechanics and corrosion rate under high and low temperature cycles of the Mg3Nd0.2Zr alloy obtained after solution treatment processes of 535-8h (535℃ insulation for 8 hours), 535-16h (535℃ insulation for 16 hours), and 535-32h (535℃ insulation for 32 hours) to illustrate the necessity of regulating the grain size.
[0033]
[0034] It can be seen from the table that the corrosion rate of the 535-16h treatment group is significantly lower than that of the other groups, which shows that the solution treatment process of this embodiment has a superior treatment effect.
[0035] See attached Figure 5, is a polarized photograph of the matrix of Mg3Nd0.2Zr alloy after 535-16h treatment. It can be seen that after 16h treatment, the grain size of the alloy is in a relatively ideal range, 10-20μm, which can ensure good corrosion resistance.
[0036] In addition, the inventors studied the high and low temperature cyclic corrosion rates of the alloys prepared under the conditions of solution treatment temperatures of 500-16h and 535-16h to illustrate the necessity of regulating the distribution of matrix elements and forming Zr-rich areas. The corrosion rates are shown in the following table:
[0037] It can be seen that the formation of Zr-rich area helps to reduce the corrosion rate of the alloy. Figure 6 and attached Figure 7 , attached Figure 7 The darker the color, the more obvious the stress in the film layer, corresponding to tensile stress or compressive stress respectively; when the heat treatment temperature is not appropriate, there is no Zr-rich area in the matrix, which makes it difficult for the Zr nucleation effect to be exerted during the corrosion process, and it is impossible to form a nano-scale shell structure, thereby failing to achieve the effect of reducing the stress concentration of the corrosion film.
[0038] This example also compares the high and low temperature cycle corrosion morphology of the new corrosion-resistant magnesium alloy shell prepared by the present invention with that of conventional ZM5, see the attached Figure 8 and attached Fig. 9 From the corrosion morphology, the traditional ZM5 alloy has obvious corrosion marks on the surface after two cycles of corrosion tests; on the contrary, the surface corrosion marks of the new corrosion-resistant magnesium alloy of the present invention are relatively shallow, indicating that the magnesium alloy of the present invention is more suitable for alternating hot and cold environments than the existing traditional alloys.
[0039] The above is an embodiment of the present invention. The above embodiments and the specific parameters in the embodiments are only for the purpose of clearly describing the invention verification process, and are not intended to limit the patent protection scope of the present invention. The patent protection scope of the present invention is still subject to its claims. Any equivalent structural changes made by using the contents of the description and drawings of the present invention should be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant magnesium alloy for a 5G base station housing, characterized in that: The alloy is composed of the following components by mass percentage: the content of Zr is less than 0.2%, the content of Nd is between 2.5-3%, and the balance is Mg; the average grain size of the corrosion-resistant magnesium alloy is 10-20 μm.
2. The corrosion-resistant magnesium alloy for a 5G base station housing according to claim 1, characterized in that: The raw materials of the corrosion-resistant magnesium alloy are Mg30Nd alloy and Mg10Zr alloy.
3. The corrosion-resistant magnesium alloy for a 5G base station housing according to claim 2, characterized in that: An island-shaped Zr-rich region is formed in the corrosion-resistant magnesium alloy.
4. Application of the corrosion-resistant magnesium alloy according to any one of claims 2 to 3 in a 5G base station housing.
5. The method for preparing the corrosion-resistant magnesium alloy according to any one of claims 2 to 3, characterized in that: The steps include: S1: proportioning the raw materials; S2: the alloy in step S1 is placed in a graphite crucible, heated to 720° C. and kept at this temperature for 30 minutes, and then further heated to 780° C., kept at this temperature for 30 minutes, and then cooled with the furnace to obtain an ingot; S3: keeping the ingot obtained in step S2 at 535° C. for 16 hours, and then quenching with 80° C. hot water; S4: keeping the material processed in step S3 at 220° C. for 32 hours, and air-cooling to obtain a corrosion-resistant magnesium alloy sample.
Citation Information
Patent Citations
A corrosion-resistant magnesium alloy
CN104264021B